THE VELOCITY STRUCTURE OF THE UPPER MANTLE AND REGIONAL DEEP THERMODYNAMICS OF THE BAIKAL RIFT ZONE - Alexander V. Pospeev (Геодинамика и тектонофизика)
The article is aimed at discussion of geological and geophysical aspects of the ‘asthenospheric’ interpretation of the ‘anomalous’ mantle layer that is revealed in the Baikal rift zone by deep seismic sounding (DSS) methods. Based on the analysis of the geoelectrical model, estimations of rheological properties, regional geothermal and deep petrological data, it is concluded that the ‘anomalous’ mantle phenomenon should be interpreted within the framework of solid-phase models. It is shown that the actual minimum depth to the top of the asthenosphere is about 60–70 km in the region under study, and temperatures at the surface of the Earth’s mantle varies from 600 to 900 °С. It is most probable that velocities are reduced in the ‘anomalous’ mantle layer due to the presence of hightemperature spinel-pyroxene facies of the mantle rocks.